Chloronychia: green nail syndrome caused by Pseudomonas aeruginosa in elderly persons - Chiriac, Anca (Clin Interv Aging, 2015)
Green nails, also known as chloronychia or green nail syndrome, are characterized by green discoloration of the nail plate (greenish-yellow, greenish-brown, greenish-black), proximal chronic non-tender paronychia, and distolateral onycholysis. The cause is Pseudomonas aeruginosa infection of the nail plate in persons whose hands are constantly exposed to water, soaps, and detergents or are subject to mechanical trauma, especially in the elderly. Green or black coloration of the nails should raise suspicion for Pseudomonas infection and be treated with an oral quinolone (ciprofloxacin), particularly in aged patients. We present three cases of green nails in elderly persons.